The role of market power in economic growth: an analysis of the differences between EU and US competition policy theory, practice and outcomes - Stephane Ciriani; Marc Lebourges (European Journal of Government and Economics (EJGE), 2016)
The European Union has experienced weak economic performance over the past 15 years, compared to the United States. In order to restore investment, innovation, and therefore growth, the European Commission seeks to raise the level of static competition in all markets. The Commission's economic policy is largely determined by its competition policy. This policy is derived from its doctrine on competition law, which regards the exercise of market power as a source of inefficiency and advocates that its effects should be banned. By contrast, the United States competition authorities, under the influence of the Chicago School, consider that market power is a necessary incentive to invest and a fair return on investment. Recent findings in economic growth theory, which state that increased competition intensity may harm endogenous innovation, provide a theoretical basis to support the United States approach and call for a review of European doctrine.
Keywords: 330; Antitrust; competition; endogenous growth; innovation; market power; market structure.